A rare case of jejunal diverticula with bone causing sub-acute intestinal obstruction - R., Akshay B.; Srivastava, Aviral; Yadav, Hari K. (International Surgery Journal, 2022)
Jejunal diverticula is a rare condition, usually remains asymptomatic though sometimes presents as vague abdominal pain and in the rare case may present as a life-threatening gastrointestinal (GI) bleed. In this case, the patient presented with features of subacute intestinal obstruction and contrast enhanced computed tomography (CECT) abdomen suggested intraluminal obstruction due to impacted bone in the small bowel. The patient underwent exploratory laparotomy, there were jejunal diverticula with bone as a foreign body, and a was ileal stricture causing an obstruction. Jejunal diverticula with bone as a foreign body is a rare case, requiring high suspicion index and relevant investigations for reaching a diagnosis.